2018
DOI: 10.4236/oalib.1104437
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Acquired Infections Caesarian Wounds in Maternity Mbuji-Mayi/DR Congo

Abstract: Introduction: The purpose of this study is to analyze the factors associated with nosocomial infections of caesarean section wounds in the maternity hospitals of the city of Mbuji-Mayi. Methods: This study was conducted in 25 maternities of general referral hospitals, clinics and hospitals in the city of Mbuji-Mayi during the period from 1 February to 1 June 2017, out of 171 parturients cesarized that were followed during a period of 4 months. A survey questionnaire was used to collect the data. Results: Out o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…Our study reported a cumulative incidence rate of HAIs of 25% (CI: The data from this study showing a high incidence of HAIs in the three main hospitals in Bobo Dioulasso are similar to those reported in previous studies in the African literature [12,[18][19][20][21]. The frequency of HAIs obtained in our study remains higher than those reported in studies from both developed countries [2,22,23] and other African studies [10,11,16,24,25].…”
Section: Discussionsupporting
confidence: 88%
“…Our study reported a cumulative incidence rate of HAIs of 25% (CI: The data from this study showing a high incidence of HAIs in the three main hospitals in Bobo Dioulasso are similar to those reported in previous studies in the African literature [12,[18][19][20][21]. The frequency of HAIs obtained in our study remains higher than those reported in studies from both developed countries [2,22,23] and other African studies [10,11,16,24,25].…”
Section: Discussionsupporting
confidence: 88%
“…Surgical site infections (SSIs) are the most common c-section-associated complication, with an estimated 10–48% of women delivering via c-section in SSA developing an SSI [ 5 6 7 8 9 10 ]. The World Health Organization (WHO) developed antibiotic prophylactic guidelines for SSI prevention [ 5 ], however, adherence to these guidelines appears low in SSA [ 11 ] with empirical antibiotic selection often based on drug availability and provider preferences [ 12 ].…”
Section: Introductionmentioning
confidence: 99%